An evaluation of poverty prevalence in China: New evidence from four recent surveys - Zhang, Chunni; Xu, Qi; Zhang, Xiaobo; Xie, Yu (International Food Policy Research Institute, 2013)
Knowledge of actual poverty prevalence is important for any society concerned with improving public welfare and reducing poverty. In this paper, we calculate and compare the poverty incidence rate in China using four nationally representative surveys: the China Family Panel Studies (CFPS) of 2010, the Chinese General Social Survey (CGSS) of 2010, the Chinese Household Finance Survey (CHFS) of 2011, and the Chinese Household Income Project (CHIP) of 2007.